Influence of socioeconomic status on access to temporal artery biopsy and rates of biopsy positivity in patients with suspected giant cell arteritis - Suellen Anne Lyne; Susan Lester; Oscar Kenneth Russell; Carlee Deanne Ruediger; Kathryn Dyer; Jem Ninan; Ernst Michael Shanahan; Catherine Louise Hill (BMC Rheumatology)
Abstract Background Data regarding the relationship between socioeconomic status (SES) and incidence of Giant Cell Arteritis (GCA) is conflicting. No previous studies have explored whether SES influences the likelihood of undergoing temporal artery biopsy (TAB). The aim of this study was to determine whether SES influences access to TAB and rate of biopsy positivity in those with suspected GCA. Methods This retrospective study included consecutive patients who underwent TAB examined at SA Pathology between 2017 and 2022; age ≥ 50 years and resident in South Australia (SA). Patients’ addresses were used to identify precise geographical areas. Area-level SES was determined using Index of Relative Socioeconomic Advantage and Disadvantage (IRSAD) scores, derived from 2016 Census data. IRSAD scores were grouped into population quintiles and analysed by multinomial regression. Results 626 participants were included, of whom 155 (25%) were TAB positive. Those with positive TAB were older (76 v 72 years) and a smaller proportion were female (63% v 71%). There was a shift towards a lower SES for patients undergoing TAB, with 161 (26%) in the lowest quintile and 107 (17%) in the highest (plinear<0.001). However, SES was not associated with TAB positivity; 34/161 (21%) participants were TAB positive in the lowest quintile compared to 33/107 (31%) in the highest (p = 0.19). Conclusion SES did not influence incidence of GCA. However, those from lower SES population quintiles were more likely to undergo TAB at a State Pathology service provider. Encouragingly, this suggests there is no issue with access to TAB in SA based on SES.